2004
DOI: 10.1128/mcb.24.12.5304-5313.2004
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity and Reduced Skin Cancer Susceptibility in Matrix Metalloproteinase 19-Deficient Mice

Abstract: Matrix metalloproteinase 19 (MMP-19) is a member of the MMP family of endopeptidases that, in contrast to most MMPs, is widely expressed in human tissues under normal quiescent conditions. MMP-19 has been found to be associated with ovulation and angiogenic processes and is deregulated in diverse pathological conditions such as rheumatoid arthritis and cancer. To gain further insights into the in vivo functions of this protease, we have generated mutant mice deficient in Mmp19. These mice are viable and fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 42 publications
(51 reference statements)
3
64
0
Order By: Relevance
“…-/-) mice were generated as previously described (18,32). Six to eight weeks-old males were sensitized by intraperitoneal injection of ovalbumin (OVA) (Sigma Aldrich, Schnelldorf, Germany) emulsified in aluminum hydroxyde (AlumInject; Perbio, Erembodegem, Belgium) on days 1 and 8.…”
Section: Mmp-19 Knock-out (Mmp-19mentioning
confidence: 99%
See 1 more Smart Citation
“…-/-) mice were generated as previously described (18,32). Six to eight weeks-old males were sensitized by intraperitoneal injection of ovalbumin (OVA) (Sigma Aldrich, Schnelldorf, Germany) emulsified in aluminum hydroxyde (AlumInject; Perbio, Erembodegem, Belgium) on days 1 and 8.…”
Section: Mmp-19 Knock-out (Mmp-19mentioning
confidence: 99%
“…Initially identified as an autoantigen in patients with rheumatoid arthritis (31), MMP-19 is a putative new molecular mediator of inflammation. The recently generated knock-out (KO) mice for MMP-19 (32,33) provide a suitable tool to decipher the potential implication of MMP-19 in allergen-induced asthma.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies using cancer models combined with selective ablation of the candidate gene in mice have thus proven to retard disease progression (Wilson et al, 1997;Itoh et al, 1998;Coussens et al, 2000), while other experiments have demonstrated that MMPs have either a limited role, or in certain instances, confer a protective role in disease progression (Masson et al, 1998;Andarawewa et al, 2003;Balbin et al, 2003;McCawley et al, 2004;Pendas et al, 2004). Collectively, these data demonstrate that the role of MMPs in disease progression is highly diverse and not solely confined to a role in tumor promotion.…”
Section: Introductionmentioning
confidence: 99%
“…A role of MMP-19 during angiogenesis is suggested by its expression in endothelial cells of synovial capillaries following injury and inflammation (3,25). However, the ex vivo sprouting of endothelial cells from aortic rings was not affected by MMP-19 deficiency (24). Therefore, the contribution of MMP-19 during angiogenic processes remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for MMP-19 involvement in tissue remodeling events, such as those occurring during adipogenesis and tumor progression, have been provided by the recent generation of MMP-19-deficient mice (24). Although lack of MMP-19 did not affect mice viability, fertility, and development, it led to a diet-induced obesity and a decreased susceptibility to skin tumors induced by chemical carcinogens.…”
Section: Introductionmentioning
confidence: 99%